A Combined Ordered Macro‐Mesoporous Architecture Design and Surface Engineering Strategy for High‐Performance Sulfur Immobilizer in Lithium–Sulfur Batteries. Issue 37 (9th August 2020) - Liu, Guihua; Luo, Dan; Gao, Rui; Hu, Yongfeng; Yu, Aiping; Chen, Zhongwei
Abstract: The practical application of lithium–sulfur (Li–S) batteries is hindered by the "shuttle" of lithium polysulfides (LiPS) and sluggish Li–S kinetics issues. Herein, a synergistic strategy combining mesoporous architecture design and defect engineering is proposed to synthesize multifunctional defective 3D ordered mesoporous cobalt sulfide (3DOM N‐Co9 S8− x ) to address the shuttling and sluggish reaction kinetics of polysulfide in Li–S batteries. The unique 3DOM design provides abundant voids for sulfur storage and enlarged active interfaces that reduce electron/ion diffusion pathways. Meanwhile, X‐ray absorption spectroscopy shows that the surface defect engineering tunes the CoS4 tetrahedra to CoS6 octahedra on Co9 S8, endowing abundance of S vacancies on the Co9 S8 octahedral sites. The ever‐increasing S vacancies over the course of electrochemical process further promotes the chemical trapping of LiPS and its conversion kinetics, rendering fast and durable Li–S chemistry. Benefiting from these features, the as‐developed 3DOM N‐Co9 S8− x /S cathode delivers high areal capacity, superb rate capability, and excellent cyclic stability with ultralow capacity fading rate under raised sulfur loading and low electrolyte content. This design strategy promotes the development of practically viable Li–S batteries and sheds lights on the material engineering in related energy storage application. Abstract : A combined 3D ordered macro‐mesoporous (3DOM) design and surface engineering strategy is introduced to develop multifunctional N‐Co9 S8− x as sulfur immobilizer for lithium–sulfur (Li–S) batteries. The S vacancies significantly promote the trapping of lithium polysulfides and its conversion kinetics, rendering fast and durable Li–S electrochemistry. The 3DOM N‐Co9 S8− x /S cathode delivers excellent performance under raised sulfur loading and low electrolyte content.